1995
DOI: 10.2307/3432529
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenesis as a Biomarker for Estrogenic Contamination of the Aquatic Environment

Abstract: A rapidly increasing number of chemicals, or their degradation products, are being recognized as possessing estrogenic activity, albeit usually weak. We have found that effluent from sewage treatment works contains a chemical, or mixture of chemicals, that induces vitellogenin synthesis in male fish maintained in the effluent, thus indicating that the effluent is estrogenic. The effect was extremely pronounced and occurred at all sewage treatment works tested. The nature of the chemical or chemicals causing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
349
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(361 citation statements)
references
References 18 publications
8
349
0
4
Order By: Relevance
“…Under normal circumstances, VTG levels in male fish are either undetectable or low (approximately 10,000 to 100,000 times lower than typical female concentrations [4,5]). However, when male fish are exposed to oestrogenic substances, they are capable of producing a large amount of VTG and blood concentrations can reach values similar to those in females.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Under normal circumstances, VTG levels in male fish are either undetectable or low (approximately 10,000 to 100,000 times lower than typical female concentrations [4,5]). However, when male fish are exposed to oestrogenic substances, they are capable of producing a large amount of VTG and blood concentrations can reach values similar to those in females.…”
Section: Introductionmentioning
confidence: 93%
“…However, when male fish are exposed to oestrogenic substances, they are capable of producing a large amount of VTG and blood concentrations can reach values similar to those in females. Thus VTG induction in male fish is commonly used as a specific biomarker for the detection of oestrogenic endocrine disruptors in the environment and in Organisation for Economic Cooperation and Development tests [6] of suspected oestrogenic chemicals [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Among those most widely used are the cytochrome P450 family of biotransforming isozymes that are induced by polycyclic aromatic hydrocarbons, polychlorinated biphenyls, dioxins and dibenzofurans (Buhler & Wang-Buhler, 1998); the metal-binding protein metallothionein, levels of which are increased by exposure to heavy metals (Olsvik et al, 2000); The inhibition of esterase activity, particularly acetylcholinesterase, caused by exposure to organophosphate and carbamate pesticides (Kirby et al, 2000;Thompson, 1999) and the yolk lipoprotein precursor vitellogenin, induced by estrogens and estrogen mimics (Sumpter & Jobling, 1995). Specific indicators of exposure are useful when the identity of a pollutant is known, or where evidence is sought for the presence of a specific pollutant.…”
Section: Introductionmentioning
confidence: 99%
“…Soto et al demonstrated that a combination of 10 chemicals enhanced the proliferation of MCF-7 cells in the E-SCREEN in a greater than additive manner (2). Sumpter and Jobling have shown that vitellogenin induction in fish hepatocytes was stimulated in a synergistic fashion by a combination of environmental chemicals (5). An in vivo example of mixtures of environmental chemicals having synergistic activity is a study using turtle eggs performed in collaboration with Bergeron et al (6).…”
mentioning
confidence: 99%